Survival Rates of Northern Bobwhite Chicks in South-Central Iowa - Willie J. Suchy; Ronald J. Munkel (National Quail Symposium Proceedings, 2017)
We estimated survival rates for radio-tagged northern bobwhite quail chicks (Colinus virginianus) in south-central Iowa from 1986 to 1988. Survival rates and survival functions were calculated for chicks from broods raised by females, broods raised by males and from broods that did not have an adult associated with them. Survival functions differed between broods with hens and those without adults. Predators accounted for almost all of the observed mortality.